Choice of nest attributes as a frontline defense against brood parasitism. (14th September 2021) - Moreras, Angela; Tolvanen, Jere; Morosinotto, Chiara; Bussiere, Elsa; Forsman, Jukka; Thomson, Robert L
Abstract: Breeding- and nest-site choice is a behavioral strategy often used to counter negative interactions. Site choices before breeding prevent costs of predation and competition but have been neglected in the context of brood parasitism. For hosts of brood parasites, the earlier brood parasitism is prevented in the breeding cycle the lower the future costs. Suitable nest-sites for cavity-nesting common redstarts ( Phoenicurus phoenicurus ), a host of the common cuckoo ( Cuculus canorus ), are a limited resource, but their cavity-nesting strategy could potentially deter predators and brood parasites. We altered the entrance size of breeding cavities and investigated redstart nest-site choice and its consequences to nest predation and brood parasitism risk, although accounting for potential interspecific competition for nest sites. We set-up paired nest-boxes and let redstarts choose between 7 cm and 5 cm entrance sizes. Additionally, we monitored occupancy rates in nest-boxes with 3 cm, 5 cm, and 7 cm entrance sizes and recorded brood parasitism and predation events. We found that redstarts preferred to breed in 5 cm entrance size cavities, where brood parasitism was eliminated but nest predation rates were comparable to 7 cm entrance size cavities. Only in 3 cm cavities both, brood parasitism and predation rates were reduced. In contrast to the other cavity-nesting species, redstart settlement was lowest in 3 cm entrance size cavities, potentially suggesting interspecific competition for small entrance size cavities. Nest-site choice based on entrance size could be a frontline defense strategy that redstarts use to reduce brood parasitism. Abstract : Nest-site characteristics impact the vulnerability of bird nests to enemies. We manipulated entrance sizes of nest-boxes and found that common redstart, a host of brood parasitic common cuckoo, preferred mid-sized entrances. Redstart entrance size preference eliminated brood parasitism but did not reduce nest predation risk. We also found that other cavity-nesting species preferred smaller entrances, suggesting that redstarts may avoid competition. We show how early season decisions can impact outcomes of host-brood parasite interactions.